Revalidación de Hyla sanborni Schmidt, 1944 (Anura: hylidae) - Basso, Néstor Guillermo (1985)
Revalidation of Hyla sanborni Schmidt, 1944 (Anura: Hylidae). Upon studies performed on populations of frog of the Hylidae family considered at present as cospeficic category: Hyla nana nana and Hyla nana sanborni, we propose a revalidation of the species Hyla sanborni Schmidt, 1944. The finding of both forms in sympatry at the Lower Delta of Paraná and at the locality of Punta Lara (NE of Buenos Aires province), the external and internal (osteocraneal) morphological differences and those found fundamentally in the structure of their mating-call provide sufficient evidence in this respect. The spectrographic analysis of the call shows that important differences both in the distribution of the spectrum formants and in the number and rhythm of emission exist. Further, the geographic distribution of H. nana, regarded typically chaqueña, has now extended to the Argentinian margin of the Río de la Plata and the Delta of Paraná.